Lanthanum and Nickel Recovery from Spent Catalyst using Citric Acid: Quantitative Performance Assessment using Response Surface Method - Petrus, Himawan Tri Bayu Murti; Wijaya, Ardyanto; Iskandar, Yusuf; Bratakusuma, Danu; Setiawan, Hendrik; Wiratni, Wiratni; Astuti, Widi (Pusat Penelitian Metalurgi dan Material - LIPI, 2018)
Heavy metals and Rare earth elements (REEs) are nowadays being used widely in many industries from electronics to petroleum industries as catalysts. However, their disposal caused serious problems to the environment. With the sharp growth in its usage, there is a better way to use and utilize valuable metals from secondary sources such as their disposal rather than using new raw materials. The aim of this work is to study the potential of citric acid as a leaching agent to extract lanthanum and nickel in various acid concentration and leaching temperature. The raw material used in this work is spent catalyst from Pertamina Refinery Unit VI, Balongan, Indonesia. The spent catalyst is decarbonized with a heat treatment at 725°C for 10 minutes before the leaching process. The leaching process used 0.1; 1; and 2 M of citric acid with a varied temperature of 30, 60, and 80°C. The lanthanum recovery was calculated by comparing the mass percentage of lanthanum before leaching process and after leaching process using Energy Dispersive X-Ray Spectroscopy (EDX). The results were analyzed by response surface methodology (RSM) and are proved to be a reliable method to depict and analyze the leaching characteristics. The molarity of the citric acid is the most significant independent variables used in the research for lanthanum recovery response. However, based on the Pareto analysis result there are no significant variables that affect the recovery of nickel. The second order polynomial fitting model is also proved to be compatible with the response of lanthanum recovery but is less compatible with nickel recovery.